The Cult of the Immaculate Conception of Mary and Argentine Laicité in the 20th Century (Quinto Sol, 2025)
Since its proclamation as dogma in 1854, the Immaculate conception played a relevant role in the dissemination of a universe of ideas and values critical of modernity. The article offers a vision of the way in which the cult of the Immaculate Conception influenced the definition of Argentine laicité in the 20th century. The study covers three moments: the celebration of the fiftieth anniversary of the definition of the dogma in 1904, the conflict between the Church and Peronism in 1954 and the decision of Carlos Menem in 1994 to restore December 8th to its status as a national holiday.
Keywords: Catholic Church; State; Laicité; Immaculate Conception